Achieving customer satisfaction through teamwork; from the perception of production and material control employees of Toshiba Electronics Malaysia Sdn Bhd / Nurfadhila Sulman - Sulman, Nurfadhila (Faculty of Business and Management, 2008)
Good teamwork is very important to many organizations. A good teamwork may propose a good result from the employees towards their working performance. This project paper is to evaluate teamwork elements facilitated by Toshiba Electronics Malaysia Sdn Bhd. The objective of this research is to identify the impact of teamwork elements/factors to the employees of Production and Material Control (PMC) department of Toshiba Electronics Malaysia Sdn Bhd in achieving customer's satisfaction. The teamwork elements under study are employee's commitment, motivation, leadership, communication and application of technology.